Artigos médicos em inglês, publicados em periódicos do Brasil e do exterior: uma análise a partir de corpora comparáveis - Perrotti-Garcia, Ana Julia (2009)
In recent years, Brazilian medical journals have increased the number of articles published in English in their issues, in an effort to attract readers from outside Brazil. Little is known about the quality of English language used in these papers, however. Two comparable corpora of approximately 5 million tokens each were collected especially for this study and contain full papers from medical journals. Corpus BRAZIL contains full papers from medical journals published in Brazil and corpus ABROAD contains full papers published in American and European medical journals, both in British English and American English. After analyzing the language used in both corpora, using WordSmith Toos (WordList, clusters; and Concord, and a script in Unix shell language, we detected that the verb submit had 1,111 occurrences in corpus BRAZIL and only 4 in corpus ABROAD. We then looked more closely at the verb submit , a prima facie translation of the Portuguese word submeter , in order to detect which grammatical structures were used in corpus ABROAD to express the same meaning. The strategies found in corpus ABROAD to express the idea studied were: use of verbs (such as undergo; receive; take; have; initiate, start, begin, use, continue, allocate, assign, attend, complete; to be taken, be referred for; perform, do, be considered for, elegible for, to be given, to be subjected to, subject to) in different tenses, voices and modes; use of adjectives; use of prepositions (after, on, with, without)